Statistical analysis of educational variables responsible for wastage in elementary education in Rajasthan - Gupta, Manoj Kumar; Prasad, jagdish (2016)
There are two goals of Sarva Shiksha Abhiyaan (SSA): universal enrolment and universal retention. Enrolment and retention in elementary education system depend upon various educational and socio-economic factors. The present article is a quantitative analysis of enrolment and dropout rates caused by various educational variables referred to as factors here. The major findings are that approach of school from home, single-teacher school, and absence of trained teachers are the main reasons affecting enrolment and dropout rates in Rajasthan. By controlling these three educational variables, dropout rate can be reduced by 20 per cent and enrolment rate can be increased by 10 per cent in the State. The data for enrolment and dropout rates and many other educational variables across the State are considered for the session 2010-11 in the study.
Keywords: Primary schools - India - Rajasthan; Primary schools